Gaza : beneath the bombs - Lock, Sharyn (Pluto ; Distributed in the United States of America exclusively by Palgrave Macmillan, 2010)
This volume presents the author's eyewitness account of what happened in the Gaza Strip during December 2008-January 2009 and in the so called following "cease fire" months. Taking the form of a diary, this book goes through 22 days of air, sea and land bombings, killings, destructions and collective punishment inflicted by the Israeli Army on the people of Gaza but also goes deep into the Gazans psyche and is full of humanity and incredibly enough, humor